Конституціоналізм і Конституція України: окремі аспекти співвідношення(дублет) - Чернецька, Олена Василівна (Державний податковий університет, 2023)
Стаття присвячена теоретико-методологічним засадам конституціоналізму та Конституції України, а також окремим аспектам їх співвідношення. Досліджується поняття конституціоналізму як складного політико-правового явища та системоутворюючої категорії конституційного права. Акцентується увага на конституціоналізмі як системі ідей і принципів, витоками якого є європейська наукова правнича думка. Конституціоналізму відводиться особливе місце в системі конституційно-правового регулювання суспільних відносин, оскільки основи конституціоналізму відображені насамперед у нормах та принципах конституції держави. Звертається увага на основні складові аспекти взаємовідношення конституціоналізму і Конституції України, а також необхідності запровадження нормативних дієвих механізмів стримань та противаг, пов’язуючи в такий спосіб конституціоналізм з обмеженням влади. Аналізується співвідношення конституціоналізму та Конституції України та їх сучасне праворозуміння в умовах української державно-правової дійсності. Власне, конституціоналізм як категорія має своє формальне вираження як норматив, який має практичне втілення в конституційний устрій держави.

The article is devoted to the theoretical and methodological foundations of constitutionalism and Constitution of Ukraine, as well as certain aspects of their relationship. It is being investigated the concept of constitutionalism as a complex political and legal phenomenon and system-forming category of constitutional law. Attention is focused on constitutionalism as a system of ideas and principles, the origins of which are European scientific legal opinion Constitutionalism has a special place in the system constitutional and legal regulation of social relations, as the foundations of constitutionalism are primarily reflected in the norms and principles of the constitution state Attention is drawn to the main component aspects of the relationship constitutionalism and the Constitution of Ukraine, as well as the need to implement normative effective mechanisms of checks and balances, linking in this way constitutionalism with limitation of power. The ratio is analyzed constitutionalism and the Constitution of Ukraine and their modern legal understanding in the conditions Ukrainian state and legal reality. Actually, constitutionalism as a category has its formal expression as a norm that has a practical embodiment inconstitutional system of the state.
Keywords: Конституціоналізм, Конституція України, верховенство права, конституційність, парламентаризм.; Constitutionalism, the Constitution of Ukraine, the rule of law, constitutionalism, parliamentarism.